Sleep Medicine and the Evolution of Contemporary Sleep Pharmacotherapy - Larrivee, Denis (IntechOpen, 2022)
Sleep is a fundamental physiological feature experienced by all known mammalian, and most non-mammalian, species. Underscoring its importance is the wide array of neural and cellular processes that have evolved to govern when and how it occurs, its duration, sequence of phases, and the influence it exerts on numerous other brain functions. This book takes up the growing prevalence of sleep disorders affecting these processes and the panorama of pharmaceutical tools that have evolved for their medical care. Its wide-ranging discussion promises not only recent updates on their clinical management but a contemporary window into sleep's cross-cutting relevance for the many neurological dysfunctions now known to associate with sleep disturbances.